WASATHIYAH (MODERASI BERAGAMA) DALAM PERSPEKTIF QURAISH SHIHAB - Sagnofa Nabila Ainiya Putri; Muhammad Endy Fadlullah (INCARE, International Journal of Educational Resources, 2022)
Quraish Shihab is one of the Indonesian Islamic thinkers who developed the concept of wasathiyah or religious moderation. This concept can be seen in his various books such as Wasathiyyah Wawasan Islam on Religious Moderation (2020), Misunderstood Islam: Dispelling Prejudice to Eradicate Errors (2019), Islam That I Understand: Diversity Is Grace (2019), Islam That I Adhered to: The Basics Islamic Teachings (2018). This study attempts to describe the concept of wasathiyah Quraish Shihab from his works. This study uses a qualitative approach to the type of library research. Primary data are 3 books of Quraish Shihab on Moderate Islam. Then analyzed by content analysis technique. Based on data analysis, it can be concluded that the concept of wasathiyyah character in the application of the appropriate concept will lead and direct humans to character and behavior that is fair and proportional in every way. In addition, Quraish Shihab also defines the concept of wasathiyyah based on several different paradigms, but all of them substantially complement each other. Among the things that are very important to note are: first, the middle position makes humans not side with the left and right. Second, the understanding of ummatan wasathan in the concept of wasathiyyah with a middle meaning in the view of God and the world. Wasathiyah also contains the main principles of fairness, balance and tolerance.